CONCEPTUAL MODEL OF ECONOMICAL SAFETY MANAGEMENT OF A PHARMACY ORGANIZATION - D. A. Kuznetsov; E. A. Korzhavykh (Фармация и фармакология (Пятигорск), 2015)
Active influence of external environment on pharmaceutical activity, and the inner processes in pharmaceutical organizations may be accompanied with certain threats appearance for economical state of an organization. In this connection, there is an objective need in administering of the safety for a pharmaceutical organization and its management basing on the corresponding knowledge. Formation of conceptual model of economical safety management of a pharmaceutical organization is the purpose of this study. Using logic analysis and generalization of literature data and the results of our studies for economical safety of pharmaceutical organizations we have revealed and characterized the principal element of a concept of “economical safety of pharmaceutical organization” and the interconnection of these elements. As the result of this study, we have formed a conceptual model of the management of analyzed subsystem of pharmaceutical management.